PENGARUH PEMBERIAN KOMPOS BUNKER DIPERKAYA DENGAN LIMBAH CAIR PABRIK KELAPA SAWIT PADA PERTUMBUHAN BIBIT KELAPA SAWIT DI BIBITAN UTAMA - Erwanda Surya; Hamidah Hanum; Chairani Hanum; Fitra Syawal Harahap (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Provision of Compost Bunkers enriched with palm oil mill effluent Aims to determine the treatment of types of compost and the treatment of NPK fertilizer doses on the provision of compost Bunkers are enriched with palm oil mill effluent on the growth of oil palm seedlings The use of compost in the main nursery is one of the most important ingredients applied in growing media. This study was carried out in the Bangun Bandar garden of PT. Socfindo, Serdang Bedagai district, Dolok Masihul sub-district with a altitude of Â± 25 m above sea level. This study used a factorial randomized block design with two treatment factors and five replications. Factor I: Compost Type that cosisted of 5 treatment levels, K0: Control, K1: Compost A (25% POME), K2: Compost B (50% POME), K3: Compost C (75% POME), K4: Compost D (100% POME). Factor II: 15-15-6-4 NPK fertilizer dosage level with 5 treatment levels: F0: F1 Control: 25% Standard Fertilization F2: 50% Standard Fertilization F3: 75% Standard Fertilization F4: 100% Fertilization Standard. The resuls showed that treatment of compost types had a very significant effect on plant height, plant hump diameter, shoot wet weight, shoot dry weight and root-shoot ratio of 25% POME. The treatment of NPK fertilizer dosage had a very significant effect on plant tuber diameter, shoot wet weight and shoot dry weight of 25-50% NPK fertilizer dosage.